2017
DOI: 10.1080/00015458.2017.1383087
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of early clinical outcomes of off-pump and on-pump coronary artery bypass grafting surgery in elderly patients

Abstract: Our results did not reveal a significant benefit of either surgical technique with respect to early-term clinical outcomes in elderly CABG patients. Further investigations are needed to determine whether off-pump CABG is superior than on-pump CABG in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
1
11
0
5
Order By: Relevance
“…Yuksel et al [ 9 ] studied patients with age of >70 years and concluded that there was no significant benefit of either technique in terms of postoperative complications and mortality. However, they did find out that off-pump CABG required significantly less transfused blood products.…”
Section: Introductionmentioning
confidence: 99%
“…Yuksel et al [ 9 ] studied patients with age of >70 years and concluded that there was no significant benefit of either technique in terms of postoperative complications and mortality. However, they did find out that off-pump CABG required significantly less transfused blood products.…”
Section: Introductionmentioning
confidence: 99%
“…A figura 1 evidencia os artigos que fizeram essa comparação, bem como a média de horas de permanência na unidade de terapia intensiva após os procedimentos. Com relação a mortalidade, 20 estudos relataram o número de óbitos, tanto no intraoperatório quanto no pós-operatório (1,10,11,12,13,15,16,18,20,21,24,26,27,28,29,32,36,37,38,41). A mortalidade total dos pacientes submetidos a CRM com CEC foi de 909 sobre 25.074 indivíduos envolvidos (3,62%).…”
Section: Resultsunclassified
“…Da mesma forma, com relação à necessidade de transfusão sanguínea, o grupo com CEC demandou maior quantidade de transfusões sanguíneas em relação ao grupo sem CEC, um dos motivos seria a hemodiluição que ocorre com o uso da CEC. Estes dados referentes às transfusões sanguíneas estiveram presentes em onze dos trinta e três artigos selecionados (10,11,12,16,19,20,21,29,37,38,41).…”
Section: Resultsunclassified
See 2 more Smart Citations